CALCULATION OF TAX REDUCTION THROUGH MANIPULATION DEPRECIATION IMPACT ON CASH FLOW OPERATING ACTIVITIES - Ekowati, Dhiana (Accounting, 2010)
This research focused on companies that reported the smallest annual profit or annual earnings changes called Suspect firm-years. In this study the authors could not find any empirical evidence showing the existence of manipulation in the calculation of depreciation of the effort made by management, in their own company respectively. The process of manipulation that is intended to reduce the debt burden of corporate taxes also do not have a significant impact on the consolidated cash flow on operasi. Depresiation activity is one way to reduce the tax burden on companies included Suspect firm-years. In this study the authors used multiple regression analysis, with three dependent variable and six independent variables, but still not proven to happen any efforts to reduce taxes by manipulating depreciation calculations made by the managers of this study do not occur company. In significant relationship between effort with tax reduction in operating cash flow, although there has been manipulation in the calculation of depreciation. Keyword : Tax, Manipulation, Depresiation, Cash Flow, Suspect firm-years, Regretion